A micro-scale analysis of suburban transformation space morphology of Mintal, Davao City - De Castro, Amor II. M. (2015)
With the rapid development of Davao?s downtown area, particularly its central business district, more and more people are moving outward to the suburbs. Mintal is one of the fast developing suburbs of Davao. In the recent decades, it has gone through a lot of developments, particularly the commercial and residential developments. Hence, this study seeks to understand the current suburban form of Mintal through the evaluation of its physical form from over the years. Moreover, it aims to determine the most suitable type of development for Mintal as an emerging urban center. This study was able to generate maps, showing a complete representation of the spatial network of barangay Mintal from 1970s up to the present. The periods taken into account were the 1970s, 1980s, 1990s, and the present. Through the use of Space Syntax Alpha Analysis, the proponent analyzed and quantified the spatial configuration of Mintal over time. Having been able to understand how the growth of its spatial structure affected the location and size of the integration core of the whole spatial system and determine the effective locations for different types of developments for the barangay, this study concluded that a commercial development is the is the most suitable for Mintal as it should cater to the needs of the growing population of the barangay and its adjacent areas with it being the commercial center of Tugbok District.